PENINGKATAN KEPEMILIKAN RUMAH SEHAT DI RT 01 DAN 03 DUSUN MODALAN KECAMATAN BANGUNTAPAN BANTUL - Dyah suryani; Shebilla Meiky Putri; Fita Nahdiyani; Encik Suci Dwi Ramadini; Nadya Trisna Gumelar Rizki; Ermila Nur Fadila; Dewi Mustika Khoirun Nisa (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2020)
A healthy home is a place of shelter, rest, and as a media for family coaching so that all family members can work productively. The condition of a healthy home is important, because an unhealthy home can have an impact on the health of its inhabitants. Indirectly an unhealthy house can increase the risk of occupants experiencing various diseases. The purpose of this activity is to describe healthy house ownership and appropriate intervention methods in RT 01 and 03 of Modalan Hamlet in Bantuntapan, Bantul. The intervention method used was education using leaflet media counseling about healthy homes. Observation results illustrate that the low level of healthy home ownership in RT 01 and 03 Modalan Hamlet. There were only 30 healthy houses out of 108 houses that were observed. The provision of interventions by counseling and giving leaflets about healthy homes cannot be measured simultaneously to see an increase in the number of healthy home ownership. Interventions must be carried out on an ongoing basis with the help of related sector approaches such as the village government, the Puskesmas and the local Health Office.